2022
DOI: 10.1371/journal.pone.0275902
|View full text |Cite
|
Sign up to set email alerts
|

Multi-isotopes in human hair: A tool to initiate cross-border collaboration in international cold-cases

Abstract: Unidentified human remains have historically been investigated nationally by law enforcement authorities. However, this approach is outdated in a globalized world with rapid transportation means, where humans easily move long distances across borders. Cross-border cooperation in solving cold-cases is rare due to political, administrative or technical challenges. It is fundamental to develop new tools to provide rapid and cost-effective leads for international cooperation. In this work, we demonstrate that isot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…47,279 Hair samples are washed in a bath of a 2:1 solution of CHCl 3 :CH 3 OH for 2 h, rinsed three times with MQ, and then airdried. 280 A baited barbed wire hair trap is used to sample the hair of wild animals. 281 The residue is dried for organic sulfur extraction by the Eschka method 282 or directly packaged for EA-IRMS measurements.…”
Section: Hairmentioning
confidence: 99%
See 1 more Smart Citation
“…47,279 Hair samples are washed in a bath of a 2:1 solution of CHCl 3 :CH 3 OH for 2 h, rinsed three times with MQ, and then airdried. 280 A baited barbed wire hair trap is used to sample the hair of wild animals. 281 The residue is dried for organic sulfur extraction by the Eschka method 282 or directly packaged for EA-IRMS measurements.…”
Section: Hairmentioning
confidence: 99%
“…Hair samples from tame animals and humans are taken by cutting from each subject at the nape of the neck about 2.5–5 cm from the scalp 47,279 . Hair samples are washed in a bath of a 2:1 solution of CHCl 3 :CH 3 OH for 2 h, rinsed three times with MQ, and then air‐dried 280 . A baited barbed wire hair trap is used to sample the hair of wild animals 281 …”
Section: Chemical Treatmentmentioning
confidence: 99%
“…The dataset generated in this study provides a baseline to track forensically relevant materials across Canada. Recent studies in Canada have already demonstrated how this database could provide key information to investigate cold cases [69,70] and reconstruct individual travel history [71].…”
Section: Forensic Applicationmentioning
confidence: 99%